FROM BRAND PLACEMENT TO TOURISM PRODUCT PLACEMENT. FICTION SERIES AS PROMOTIONAL SUPPORT OF TOURISM DESTINATIONS - Noelia Araújo-Vila; José Antonio Fraiz-Brea (Enlightening Tourism: A Pathmaking Journal)
Fiction series are an audiovisual product which is part of a major industry, entertainment industry. Every day more consumers spend much of their free time to the consumption of such products, which is reflected in the notable increase in downloads and audiences. Therefore, many industries have decided to use audiovisual series as advertising, being one tourism sector. There are many destinations worldwide who have decided to set in a fiction series, thus being viewed by thousands of spectators, which has resulted in increases in visitors. Finally, in order to facilitate visits by tourists through recording areas, tourism products have also emerged related to the series, the movie maps of series.